Infectious agents in the pathogenesis of rosacea - Mehrholz, Dorota M.; Nowicki, Roman; Barańska-Rybak, Wioletta M. (Dermatology Review/Przegląd Dermatologiczny, 2016)
Acne rosacea is a chronic inflammatory skin disease that affects the face. The symptoms depend on the stage of the disease. The first stage is characterized by erythema and telangiectasia. This is followed by a papulopustular phase and a phymatous type in the final stages. An ocular type of rosacea is described in the literature as well. In the etiopathogenesis of papulo-pustular and ocular types of rosacea, inflammatory response modulation caused by microorganisms living on the skin play a key role. Binding of bacterial ligands with epidermal receptors leads to induction of the inflammatory cascade. This leads to vasodilation and white blood cell chemotaxis, which causes a change in the microenvironment of the skin that assists in microorganism proliferation. Microorganisms such as Demodex folliculorum, Bacillus oleronius, Staphylococcus epidermidis, Chlamydia pneumoniae and Helicobacter pylori play a crucial role in the pathogenesis of rosacea.